Enhancement of Hot Corrosion Resistance of Modified 9Cr-1Mo Steel Through Surface Nanostructuring and Pre-oxidation - Sri Bandla D.; Verma P.; Chattopadhyay K.; Singh V. (My University, 2025)
Nanosize grains of ~ 65 nm were developed with large misorientation angles of grain boundaries in surface region of normalized and tempered modified 9Cr-1Mo steel by ultrasonic shot peening (USSP) with hard steel balls of 3 mm diameter. The surface roughness and the depth of nanostructured surface region were found to increase with the duration of USSP from 0.5 to 5 min. Hot corrosion tests were performed for the Un-USSP and the samples USSPed for the durations of 0.25 and 1.5 min and also for the samples subjected to USSP and subsequently pre-oxidation at 600 °C for 4 h. The hot corrosion resistance at 600 °C under 100% NaCl coating was significantly improved by USSP for 1.5 min and subsequent pre-oxidation at 600 °C for 4 h. The results are discussed in terms of the formation of more uniform and effective protective iron–chromium oxide layer on the USSPed surface from the subsequent pre-oxidation treatment, prior to hot corrosion of the specimens under 100% NaCl coating at 600 °C. © 2018, ASM International.